Study on the Impact of Applying Blockchain Technology in the Processes of the Health Industry Especially in the Field of Health Oriented Products. Case Study: Health Industry Society of Isfahan City - Mirshamsi, F. (Issues and Development in Health Research Vol. 7, 2021)
Nowadays, the health industry is one of the largest industries in the world which includes more than 10% of gross domestic product in developed countries. Health industry consists of patient information management subsets, pharmaceutical and biomedical research, prescription and drug use management, medical records and test results, telemedicine, claim and payment of health insurance, supply chain management agent set, production, marketing, distribution, Sales, communication with stakeholders, internal and external commerce, monitoring and tracking of health-oriented products, especially human medicine. The many challenges that disrupt the effective processes in healthcare operational cycles have been identified and analyzed in this paper, to identify the impact of applying emerging blockchain technology solutions and their benefits, especially in health-centric businesses. Increasing growth of information technology, information science and its applications, especially the emergence and penetration of blockchain technology, not only have benefits for production, sales, support and supervision of health-oriented products, especially human-based medicines, but also can transform information and communication infrastructures, blockchain-based systems, capabilities, accuracy, speed and trust in health industry systems and in the supply of raw materials and requirements, marketing , sales, customer relationship management, Standards, Requirements and Supervisory Levels Drugs in organizations, companies and individuals involved in this industry with creating new business models, the annoying challenges will be fixed then the health industry of the world will transform. Research Methodology: By conducting open interviews with health industry experts, the process of identifying and determining independent and dependent variables, a questionnaire was designed based on the objectives and hypotheses of the research and then the validity and reliability of the questionnaire by surveying experts and pre-test, case was reviewed and approved. The results were analyzed and interpreted by distributing, completing and collecting questionnaires and performing statistical analysis on the data using SPSS 26. Findings and Conclusions: Applying solutions based on blockchain technology and Utilizating its benefits for the components of the health industry, including a system for tracking, tracking and controlling the authenticity of health-oriented goods, electronic health record system and competitiveness in international and global trade, is a necessary, meaningful and With a positive effect.